Anti‐CD40 ligand monoclonal antibody delays the progression of murine autoimmune cholangitis. (24th October 2013) - Tanaka, H.; Yang, G.‐X.; Iwakoshi, N.; Knechtle, S. J.; Kawata, K.; Tsuneyama, K.; Leung, P.; Coppel, R. L.; Ansari, A. A.; Joh, T.; Bowlus, C.; Gershwin, M. E.
Summary: While there have been significant advances in our understanding of the autoimmune responses and the molecular nature of the target autoantigens in primary biliary cirrhosis (PBC), unfortunately these data have yet to be translated into new therapeutic agents. We have taken advantage of a unique murine model of autoimmune cholangitis in which mice expressing a dominant negative form of transforming growth factor β receptor II (dnTGFβRII), under the control of the CD4 promoter, develop an intense autoimmune cholangitis associated with serological features similar to human PBC. CD40‐CD40 ligand (CD40L) is a major receptor–ligand pair that provides key signals between cells of the adaptive immune system, prompting us to determine the therapeutic potential of treating autoimmune cholangitis with anti‐CD40L antibody (anti‐CD40L; MR‐1). Four‐week‐old dnTGFβRII mice were injected intraperitoneally with either anti‐CD40L or control immunoglobulin (Ig)G at days 0, 2, 4 and 7 and then weekly until 12 or 24 weeks of age and monitored for the progress of serological and histological features of PBC, including rigorous definition of liver cellular infiltrates and cytokine production. Administration of anti‐CD40L reduced liver inflammation significantly to 12 weeks of age. In addition, anti‐CD40L initially lowered the levels of anti‐mitochondrial autoantibodies (AMA), but these reductions were not sustained. These data indicate that anti‐CD40L delays autoimmune cholangitis, but the effect wanes over time. Further dissection of the mechanisms involved, and defining the events that lead to the reduction in therapeutic effectiveness will be critical to determining whether such efforts can be applied to PBC.